Description of two new species of Polypedilum (Asheum) and immature stages of Polypedilum (A.) curticaudatum (Diptera: Chironomidae) - Pinho, Luiz Carlos; Da Silva, Fabio Laurindo (Zootaxa, 2020)
Two new species of Polypedilum (Asheum) (Diptera: Chironomidae: Chironominae) are described and figured as adult males, P. (A.) sofiae sp. n. collected in the states of Mato Grosso and Rondônia and P. (A.) mayrahu sp. n. collected in the state of Bahia, Brazil. In addition, the adult male of Polypedilum (Asheum) curticaudatum (Rempel) is redescribed based on material from some localities in the Brazilian Atlantic Forest and Pantanal, and its larva and pupa are described for the first time.